Micro-scale molten salt and metal reactor for space applications - Jaehyun Ryu; Yonghee Kim (Nuclear Engineering and Technology, 2025)
This paper introduces a novel reactor concept called Molten Salt Metal Reactor (MSMR), specifically designed for space applications. This innovative reactor leverages a uranium alloy liquid metal as fuel, integrating the advantages of traditional Molten Salt Reactors (MSRs) while achieving criticality in a compact size and enabling long operational lifespans without the need for refueling. To adapt the MSMR for extra-terrestrial use, we employed high-assay low-enriched uranium (HALEU) and heat pipes, followed by comprehensive optimizations to ensure a compact reactor design that delivers both high power and longevity. Our study focuses on assessing the feasibility of the proposed MSMR design through detailed neutronic and thermal-hydraulic analyses. Utilizing the Monte Carlo code Serpent 2 for neutronics and COMSOL 6.2 for thermal-hydraulics, we evaluated the reactor's performance under a 500kWth condition. The results show that the reactor achieves an operational lifetime of approximately 36 years. Safety evaluation confirms a negative fuel temperature coefficient (−3 pcm/K), an excess reactivity of less than 1$, and a shutdown margin exceeding 7100 pcm under cold conditions. Our findings suggest that the MSMR is a promising candidate for space applications, combining long life, structural simplicity, and superior safety features inherent to MSRs.